Pengaruh Profitabilitas dan Kepemilikan Institusional Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderasi Pada Perusahaan Property dan Real Estate di BEI Periode 2015-2018 - Tatas Ridho Nugroho; Umi Muawanah; Djuni Farhan (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2020)
This research aims to determine and analyze the effect of profitability and institutional ownership on firm value with capital structure as a moderating variable in Property and Real Estate Companies on the IDX for the 2015-2018 period. This research is a quantitative research. The data source used is the data source. secondary. data is obtained indirectly and through intermediary media. The type of data used in this research is external data in the form of time series data. The data in this study are in the form of annual reports obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The population in this study were 48 companies. The sampling technique was done by using purposive sampling technique, the number of companies used as a sample was 25 companies and the data obtained were 100 data. Data analysis was performed through the SPSS program. The data analysis methods used were: descriptive statistical test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that the profitability variable proxied using ROE (Return on Equity) has an effect on firm value, institutional ownership variable has no effect on company value, profitability and institutional ownership variables jointly affect firm value, capital structure variable can moderate and strengthening the relationship between profitability to firm value and capital structure variables are unable to moderate the relationship between institutional ownership and property and real estate company value listed on the Indonesia Stock Exchange for the period 2015-2018.